Book design politics in the context of new technologies (Estudos em Design, 2023)
Graphic design is a mediation process that involves project choices and decisions, which carry invisible dimensions and intentions, such as the ideologies that defines them. In present times, this mediation process is more complex, as new production and consumption arrangements take place. This paper seeks to discuss questions concerning book design in the context of new technologies, from theoretical and practical approaches, in a political perspective, raising reflections on the need for a conscious and responsible practice in search of a more ethical society. It also presents considerations about writing and typography, images, technologies and devices, business model, algorithms, and some trends and perspectives of the publishing market. The paper concludes by stating that the editorial design process, essentially in the contemporary scenario of new technologies, has to be carried out from a critical and political stance, considering the factors that influence praxis and compose the complexity of the editorial context.
Keywords: Editorial design; Technologies; Politics